Analysis of the smash and footwork performance of men's singles athletes at the 2021 toyota Thailand open - Adzinar Rasyid; Prasetyo, Heru; Imam Wahyu Nalendra; Aditya Dwi Prima Nanda; Danang Armando Prakoso; Muhammad Bima Akasy; Alwan Priyan Ananta; Novica Anzar Sunarno; Rahmat Basuki; Delvieri Syafril; Fidelis Finishtian Krisna (Departement of Sports Coaching, Faculty of Sports Sciences, Universitas Negeri Yogyakarta, 2023)
This study aims to analyze the success rate of smash techniques and dominant footwork patterns in the men's singles semifinals and finals of the 2021 Toyota Thailand Open. The study used a quantitative descriptive method with four male singles athletes who competed in the semifinals and finals as subjects. Data collection was conducted through observation using a smash technique and footwork analysis instrument sheet, while data analysis used descriptive statistics in the form of percentages. The results showed that the success rate of smash techniques in the semifinals and finals was very high. Full smashes, cut smashes, whip smashes, and circular smashes had a success rate of over 90%, while backhand smashes were rarely used in the finals. In addition, the most dominant footwork pattern was movement to the left rear, both in the semifinals and finals. These findings indicate that the effectiveness of smashes and the dominance of certain footwork patterns play a significant role in athletes' performance at the world level. The research results are expected to serve as evaluation material and a reference for coaches and athletes in developing training programs that are more aligned with the actual needs of competition.